WHO LIVES WHERE? LIVING SITUATION AND COMPARATIVE NEEDS OF OLDER ADULTS. (11th November 2018) - Karon, S; Toth, M; Palmer, L; Bercaw, L; Johnson, R; Jones, J; Love, R
Abstract: As the population ages, there is a need to better understand the types of assistance people need and where they receive it, whether in their own homes, in nursing homes, or, increasingly, in community-based residential care settings (e.g., assisted living facilities) that offer access to long-term services and supports. We estimated the United States older adult population, their places of residence, and their demographic, health, and functional characteristics using multiple data sources: the Medicare Current Beneficiary Survey 2008 and 2013 Cost and Use Files; Health and Retirement Survey 2008 and 2014; National Health and Aging Trends Study 2011 and 2015; and the National Study of Long Term Care Providers 2010, 2012, and 2014. The number of people living in community-based residential care has increased over time, but estimates vary by survey. However, with a few key exceptions, the demographic characteristics of residents are similar across years and datasets. In all data sources, and at all points in time, people living in community-based residential care settings reported more impairments than did those living in traditional settings. People living in community-based residential settings were similar, in many ways, to those living in nursing homes. In all settings, the proportion of people with dementia increased over time. These patterns were consistent across data sets. The share of older adults living in community-based residential care settings is increasing, along with their health and functional needs. Whether these setting have the staffing or expertise to meet these care needs is an important policy consideration.